PHArmacists' perspective oN the Take hOme naloxone prograM (The PHANTOM Study). (July 2017) - Edwards, Jenny; Bates, Duane; Edwards, Brett; Ghosh, Sunita; Yarema, Mark
Objective: To evaluate pharmacists' attitudes toward the Take Home Naloxone (THN) program and identify areas that could be improved to support pharmacists' involvement. Methods: Pharmacists on the Alberta College of Pharmacists' directory were invited to complete an online survey between July 10 and August 8, 2016. The survey consisted of 19 questions. Descriptive statistics were used to analyze the data. Results: Four hundred seventy pharmacists completed the survey (response rate = 11.2%). A total of 76.8% of respondents strongly agreed or agreed that pharmacists should be screening patients to identify those at risk of opioid overdose. Full-time pharmacists were more likely to agree ( p = 0.02). A total of 79.8% of respondents strongly agreed or agreed that pharmacists should be recommending THN kits. Pharmacists working in large population centres ( p = 0.008) and full-time pharmacists ( p = 0.02) were more likely to agree with this statement. Furthermore, 60.6% of pharmacists were extremely willing or very willing to participate in the THN program. Pharmacists in practice for ≤15 years were more willing to participate in the THN program than pharmacists in practice >15 years ( p = 0.03). The most common perceived barriers to implementation of the THN program were lack of time in pharmacists' current work environment and education about the program. Conclusions: Overall, pharmacists had positive attitudes toward screening patients to identify those at risk of opioid overdose, recommending THN kits and willingness to participate in the program. Factors that may facilitate increased participation in the program include addressing time issues and improving education about the THN program.